Phân tích tác động của đổi mới sáng tạo đến kết quả kinh doanh của các ngân hàng niêm yết trên sàn chứng khoán Việt Nam - Nguyen An , Huy; Kim Huong , Trang (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
This study investigates the impacts of innovation activities on the business performance of 18 commercial banks listed on the Hanoi Stock Exchange (HNX) and the Ho Chi Minh Stock Exchange (HOSE) from 2010 to December 31, 2020. The results of the multivariate regression models have found that the innovation process has a positive impact on the business performance of banks. However, organizational innovation has a negative influence on business results. Surprisingly, product innovation does not have a statistically significant relationship with the business performance of listed banks.